2020
DOI: 10.14198/jhse.2022.171.09
|View full text |Cite
|
Sign up to set email alerts
|

Association between vertical and horizontal force-velocity-power profiles in netball players

Abstract: Netball is a collective sport characterized by intermittent high-intensity actions. Therefore, the players must develop high levels of relative bilateral and unilateral strength and power for both improve performance and also reduce injury risk. The purpose of this study was (i) to provide a reference about the mechanical outputs obtained in the vertical (jumping) and horizontal force-velocity-power (FVP) profile and (ii) observe their relationship, besides the performance in jumping and sprinting in amateur f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Samozino et al [52] recently identified acceleration performance less than 30m largely depends on P MAX and individual mechanical characteristics, further identifying the necessity to develop and express this mechanical quality to be an effective field hockey player. These findings have been supported in similar studies, but not all (r = 0.27) [53] involving amateur netball players, academy rugby players, high-level sprint athletes and professionl male and female football players, (r = 0.40−0.75) [14,[18][19][20], further highlighting the need for power development expression in field and court sports. However, across these studies, most force variables (F 0 ) did not achieve significance (r ≤ 0.27), thereby demonstrating a greater emphasis on movement velocity capabilities to express maximal external power.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Samozino et al [52] recently identified acceleration performance less than 30m largely depends on P MAX and individual mechanical characteristics, further identifying the necessity to develop and express this mechanical quality to be an effective field hockey player. These findings have been supported in similar studies, but not all (r = 0.27) [53] involving amateur netball players, academy rugby players, high-level sprint athletes and professionl male and female football players, (r = 0.40−0.75) [14,[18][19][20], further highlighting the need for power development expression in field and court sports. However, across these studies, most force variables (F 0 ) did not achieve significance (r ≤ 0.27), thereby demonstrating a greater emphasis on movement velocity capabilities to express maximal external power.…”
Section: Discussionmentioning
confidence: 57%
“…The stronger kinematic relationship between relative P MAX and v 0 in sprinting compared to jumping is likely due to the necessity to achieve maximal power expression in early acceleration [58] plus the overall duration of the task places a greater emphasis on velocity qualities. Similar P MAX correlations in other population groups including netball, soccer and ballet suggests this relationship may be typical amongst athletes irrespective of their ability level or sport (i.e., novice vs elite) [14,[18][19][20][21].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The benefits of FVP profiling include addressing variability in playing level [4,5], sport position [6], and age [7] as well as the ability to take into account external variables, such as time of season [8]. Team sports, such as rugby [3,9], soccer [4,7], ice hockey [10], and netball [11], as well as individual athletic activities, such as ballet [12] and gymnastics [13], have utilized this approach.…”
Section: Introductionmentioning
confidence: 99%